Kesehatan Diri Dan Lingkungan : Pentingnya Gizi Bagi Perkembangan Anak - ., Rahmi Fuji Hidayah; ., Meta Octa Riany; ., Sarmila; ., Yecha febrianita Putri (CV. ITTC INDONESIA, 2023)
Children are the next generation and are the foundation of the future for the nation and state. With the promotion of human resources at this time, children are also one of the targets of HR. In order for children to grow and develop normally, the role of nutrition is very necessary and must be considered. By fulfilling nutritional needs, such as carbohydrates as a source of energy (energy), protein as a building agent and vitamins/minerals as a regulatory substance, it will help prevent disease. which results in inhibiting the growth and development of children. Proper nutritional composition will spur growth and development, good food is food that is adjusted to the age level and type of activity. With the fulfillment of nutritional needs, it is hoped that the elements of maintenance, growth, repair of damaged or lost bodies, reproduction, physical work and Specific Dynamic Action (SDA) will also be good.